1992
DOI: 10.1111/j.1476-5381.1992.tb14272.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of a receptor for calcitonin gene‐related peptide on rat, L6 myocytes

Abstract: 1 The L6 myocyte cell line expresses high affinity receptors for calcitonin gene-related peptide (CGRP) which are coupled to activation of adenylyl cyclase. The biochemical pharmacology of these receptors has been examined by radioligand binding or adenosine 3':5'-cyclic monophosphate (cyclic AMP) accumulation. 5 The pharmacological profile of the L6 CGRP receptor suggests that it most closely resembles sites on skeletal muscle, cardiac myocytes and hepatocytes. The L6 cell line should be a stable homogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 35 publications
11
83
0
Order By: Relevance
“…The relative potencies of these peptides for these responses in rat soleus muscle were similar to their reported relative affinities for amylin receptors identified in rat brain . These findings are consistent with recent results suggesting that amylin activates adenylylcyclase coupled receptors in rat soleus muscle (Pittner et al, 1995a) amylin receptors identified in rat brain (Beaumont et al, 1995b) and distinct from CGRP receptors (Yamaguchi et al, 1988;Poyner et al, 1992). In contrast to the pattern seen in soleus muscle, the order of potency for cyclic AMP generation and inhibition of ["C]-glycogen formation in both L6 and C2C12 cells was CGRP> >rat amylin> >salmon calcitonin.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The relative potencies of these peptides for these responses in rat soleus muscle were similar to their reported relative affinities for amylin receptors identified in rat brain . These findings are consistent with recent results suggesting that amylin activates adenylylcyclase coupled receptors in rat soleus muscle (Pittner et al, 1995a) amylin receptors identified in rat brain (Beaumont et al, 1995b) and distinct from CGRP receptors (Yamaguchi et al, 1988;Poyner et al, 1992). In contrast to the pattern seen in soleus muscle, the order of potency for cyclic AMP generation and inhibition of ["C]-glycogen formation in both L6 and C2C12 cells was CGRP> >rat amylin> >salmon calcitonin.…”
Section: Discussionsupporting
confidence: 91%
“…amylin is at least as potent as CGRP, and salmon calcitonin is most potent in effects on glycogen metabolism (Beaumont et al, 1995b;Young et al, 1995). This is in sharp contrast to the pattern of interaction of these ligands with CGRP receptors, which bind CGRP best, bind amylin with -100 fold lower affinity, and bind salmon calcitonin very weakly, if at all (Yamaguchi et al, 1988;Poyner et al, 1992).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…␣CGRP in the range 10 pM to 1 M was added for a further 15 min. Ice-cold ethanol (95-100% v/v) was used to extract cAMP, which was subsequently measured by radioreceptor assay as previously described (16) Analysis of Cell-surface Expression of Mutants by Enzyme-linked Immunosorbant Assay (ELISA)-Cells in 12-well plates were transiently transfected with wild type (WT) or mutant HA epitope-tagged human CL and RAMP 1. The transfected cells were treated with 3.7% formaldehyde for 15 min after aspiration of growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…In preliminary studies (Poyner et al, 1993) we have identified cAMP as the intracellular transducer involved in secretory responses in HCA-7 and Col-29 epithelia, showing similar time-dependent, sustained increases in cAMP production in response to ra-CGRP. Elevation of adenylate cyclase activity is the most common transduction mechanism observed following CGRP stimulation (Poyner et al, 1992;Stangl et al, 1993), though there is evidence in skeletal muscle cells of an increase in inositol phosphate production (Laufer & Changeux, 1989). Type 1-like CGRP receptors have been identified in rat epididymal cells in culture, in which CGRP increases the s.c.c.…”
Section: Agonist Concentration-response Relationshipsmentioning
confidence: 99%